Just One Thing: Twelve of thw Qorld's Best Investors Reveal the One Strategy You Can't Overlook - Mauldin John (John Wiley & Sons, 2006)
Just one more thing : there are alot of great idears in the next few hundred pages, but you have to put them into practice. So as you read, think about how to put you will put the principles, tips, and ideas to use in your personal life. And that you will make this book be a very good thing.